Quality of life, social function, emotion, and facial paresis in Dutch vestibular schwannoma patients - Blom, Stephanie (2020)
The present study aimed to replicate the finding that vestibular schwannoma (VS) patients with facial paresis experience lower health related quality of life (QoL) than those without facial paresis in a Dutch sample, and to extend these findings by measuring VS patients' overall satisfaction with life, social function, and emotion.